"Al-Quran tafsir pimpinan Ar-Rahman" software - Abdul Wahid, Fauziah; Mazlan, Ahmad Akmaluddin; Ab. Wahab, Auni Hazimah; Ismail, Roesnita; Md Norwawi, Norita (Universiti Teknologi MARA, Kedah, 2017)
Information Retrieval (IR) plays important role in retrieving information related to the needs of a person. The invention of computer has made the task of retrieving information much easier and faster. However, there is a problem in retrieving information using computer. For example, if a person types “Malay Quran translation” in a search engine, it will retrieve a mass amount of results that is called hits. Even though it contains the relevant information that a person needs, it is impossible for the person to look at all links. This problem in IR triggers the idea for this software that involves al-Quran translation, which is widely used in Malaysia. The content of al- Quran is related to all aspect of lives and it should be included in all research disciplines, where this has been practice worldwide. To date, al-Quran translation is mostly being used by scholars in Islamic field whereas it should be expanded to all type of field. But scholars in other than Islamic field find it difficult to search for relevant Ayah in al-Quran translation from an authenticated source and also by using a reliable search engine or software.Al-Quran translations available in Malaysia includes Pimpinan Ar-Rahman, which is an al-Quran translation version endorsed by Department of Islamic Development, Malaysia (JAKIM). The justification for adopting Pimpinan Ar-Rahman for this software is because it has been widely referred in various researches by Malaysian scholars with approximately 162 citations (information obtained through Google Scholar as 22th August 2017). There are a number of versions of Pimpinan Ar-Rahman including Roman Malay, Jawi Malay and English. However, this software will be in Roman Malay as it is the national language of Malaysia and the software is intended not only for researcher but also for layman as well to be use in their daily life.